Analysis Of Voltage Regulation Methods in Low-Voltage Electric Networks - Bokhodirov Islomjon Abdulaziz ugli; Ibroximjonov Ahliddin Baxtiyorjon ugli (Genius Journals, 2023)
This article examines the scientific basis of voltage adjustment methods to ensure reliability of power supply. The purpose of this is to provide continuous, high-quality electricity supply to modern enterprises with complex technological processes and existing energy system networks. Through the proposed methods, it is possible to control the voltage loss and drop between the generation and consumption of electricity
Keywords: Quality indicators of electric power; voltage losses; methods of voltage adjustment